Combination of nucleic acid amplification and CRISPR/Cas technology in pathogen detection - Zeng, Dandan; Jiao, Jinlong; Mo, Tianlu (Frontiers in Microbiology, 2024)
Abstract：Major health events caused by pathogenic microorganisms are increasing, seriously jeopardizing human lives. The most widely used polymerase chain reaction and isothermal nucleic acid amplification technologies have been developed for rapid detection in food, medicine, industry and agriculture, and play an important role in safeguarding human health. However, due to the non-specificity of the amplification process, researchers have proposed the combination of nucleic acid amplification technology with the novel technology CRISPR for detection, which improves the specificity and accuracy of the results. This paper summarizes the research progress of nucleic acid amplification technology in conjunction with CRISPR/Cas technology for the detection of pathogens, which provides a reference and theoretical basis for the subsequent application of nucleic acid amplification technology in the field of pathogen detection.